Decreased Post-Cesarean Endometritis Following Povidone Iodine-Vaginal Preparation - Raheem Kareem , Alaa; Munim, Wasan; Kamel, Niran; Rasool Aal- Saleh, Mustafa; Abdulkareem Ali Al-Dujaili, Sarah; Luay Subhi, Mohammed (Diyala Journal of Medicine, 2020)
Background: Despite the use of several strategies to prevent post-Cesarean complications including wound infections and endometritis, they remain high morbidities. Objective: To assess the pre-Cesarean preparation of the vagina with povidone iodine as a preventive measure against post-cesarean wound infection and endometritis. Patients and Methods: A case-control study conducted on 200 pregnant women who prepared for elective Cesarean section. The operations were conducted either with standard classical abdominal scrub alone (as control group) or vaginal povidone iodine preparation in addition to the standard abdominal scrub. Each woman was followed up post-operatively for development of fever, endometritis, and wound infection, duration of postoperative antibiotics administration, and postoperative stay. Results: Post-Cesarean endometritis developed in 6% of women who received a vaginal preparation pre-operatively and 15% of the controls. 30% of control women and 20% of women in the treatment group had post-operative febrile illness. Wound infections were uncommon complications that occurred only in two percent of the control patients and one percent of patient in the treatment group. Conclusion: Pre-operative vaginal treatment with povidone iodine decreased the risk of post-Cesarean endometritis. However, this protocol doesn't decrease the whole risk of post-operative wound infection or fever.